An Integrated Collaborative Learning and Polya Problem-Solving Model for Enhancing Pre-Service Teachers’ Engagement, Attitudes, Critical Thinking, and Perceptions in Mathematical Problem-Solving - Isaiah Dookurong Dilor; Yarhands Dissou Arthur; Akweittey Emmanuel (International Journal of Mathematics and Mathematics Education, 2026)
Purpose - This study examined the effect of integrating collaborative learning with George Pólya’s problem-solving approach on pre-service teachers’ attitudes, engagement, and critical thinking skills in mathematics. Guided by a pragmatist paradigm, the study aimed to generate practical insights for improving teaching and learning in mathematics education. Methodology - A sequential explanatory experimental design was adopted. The population comprised 15,600 pre-service mathematics teachers, from which a purposive sample of 390 participants was selected using the Yamane formula. Participants were divided into treatment and control groups. The treatment group received a six-week intervention using the integrated collaborative learning and Polya problem-solving model, while the control group received conventional instruction. Quantitative data were collected using a critical thinking achievement test and structured questionnaires measuring attitudes and engagement, while qualitative data were obtained through open-ended responses and classroom observations. Quantitative data were analyzed using independent samples t-tests, and qualitative data were analyzed thematically following Braun and Clarke’s six-phase framework. Findings - The integrated instructional approach significantly improved pre-service teachers’ attitudes toward mathematics, enhanced engagement in learning activities, and strengthened critical thinking skills. Qualitative evidence highlighted that collaborative interaction, sustained participation, and reflective discussions supported deeper understanding and higher-order thinking. Novelty - The study provides empirical evidence for the combined effect of collaborative learning and Polya’s problem-solving framework in enhancing both cognitive and affective outcomes in pre-service mathematics education. Significance - Findings are relevant to mathematics educators, teacher trainers, and curriculum developers seeking evidence-based strategies to promote engagement, positive learning dispositions, and critical thinking among pre-service teachers.